Association Between the Implementation of Shared Decision-Making and Clinical Characteristics of Living-Donor Kidney Transplantation - Akito Mochizuki; Kazuhiro Tada; Sho Shimamoto; Koji Takahashi; Kenji Ito; Yoko Yokoyama; Masahiro Tachibana; Nobuyuki Nakamura; Nobuhiro Haga; Kosuke Masutani (Healthcare, 2026)
Background/Objectives: Shared decision-making (SDM), which incorporates patients’ values and preferences, may support patient-centered selection of renal replacement therapy, but its association with the clinical characteristics of living-donor kidney transplantation (LDKT) remains unclear. This study aimed to evaluate the association between SDM implementation and the clinical characteristics of LDKT. Methods: A specialized SDM outpatient clinic was established at our institution in 2019. We retrospectively analyzed 65 patients who underwent LDKT at a single center between 2010 and 2025, comparing a pre-SDM group (2010–2018, n = 25) with a post-SDM group (2019–2025, n = 40). Results: Recipient characteristics were similar between groups, whereas donors were older after SDM implementation (62.0 [52.3–68.0] vs. 55.0 [44.5–60.0] years; p = 0.01). ABO-incompatible transplantation (37.5% vs. 4.0%; p = 0.003) and preformed donor-specific antibody-positive transplantation (20.0% vs. 0%; p = 0.02) were more frequent in the post-SDM group. The proportion of preemptive kidney transplantation (PEKT) was similar; however, among PEKT recipients, estimated glomerular filtration rate was higher at initial evaluation and admission, and preoperative dialysis was numerically less frequent in the post-SDM group (20.0% vs. 54.5%; p = 0.106). Conclusions: Implementation of the SDM clinic was associated with a higher frequency of immunologically complex LDKT and better-preserved kidney function at initial transplant evaluation and admission among PEKT recipients. These associations should be interpreted cautiously given potential secular changes in transplant practice.